Endogenous epoxygenases are modulators of monocyte/macrophage activity. - Jonas Bystrom; Jessica A Wray; Mary C Sugden; Mark J Holness; Karen E Swales; Timothy D Warner; Matthew L Edin; Darryl C Zeldin; Derek W Gilroy; David Bishop-Bailey (PLoS ONE)
Background Arachidonic acid is metabolized through three major metabolic pathways, the cyclooxygenase, lipoxygenase and CYP450 enzyme systems. Unlike cyclooxygenase and lipoxygenases, the role of CYP450 epoxygenases in monocyte/macrophage-mediated responses is not known. Methodology/principal findings When transfected in vitro, CYP2J2 is an efficient activator of anti-inflammatory pathways through the nuclear receptor peroxisome proliferator-activated receptor (PPAR) α. Human monocytes and macrophages contain PPARα and here we show they express the epoxygenases CYP2J2 and CYP2C8. Inhibition of constitutive monocyte epoxygenases using the epoxygenase inhibitor SKF525A induces cyclooxygenase (COX)-2 expression and activity, and the release of TNFα, and can be reversed by either add back of the endogenous epoxygenase products and PPARα ligand 11,12- epoxyeicosatrienoic acid (EET) or the addition of the selective synthetic PPARα ligand GW7647. In alternatively activated (IL-4-treated) monocytes, in contrast to classically activated cells, epoxygenase inhibition decreased TNFα release. Epoxygenases can be pro-inflammatory via superoxide anion production. The suppression of TNFα by SKF525A in the presence of IL-4 was associated with a reduction in superoxide anion generation and reproduced by the superoxide dismutase MnCl(2). Similar to these acute activation studies, in monocyte derived macrophages, epoxygenase inhibition elevates M1 macrophage TNFα mRNA and further decreases M2 macrophage TNFα. Conclusions/significance In conclusion, epoxygenase activity represents an important endogenous pathway which limits monocyte activation. Moreover endogenous epoxygenases are immuno-modulators regulating monocyte/macrophage activation depending on the underlying activation state.